1974
DOI: 10.1083/jcb.62.1.132
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLE GENE SITES FOR 5S AND 18 + 28S RNA ON CHROMOSOMES OF GLYPTOTENDIPES BARBIPES (STAEGER)

Abstract: Ribosomal RNAs (28 + 18S and 5S) and 4S RNA extracted from the chironomid Glyptotendipes barbipes were iodinated in vitro with 125I and hybridized to the salivary gland chromosomes of G. barbipes and Drosophila melanogaster. Glyptotendipes. Most of the label produced by this RNA was localized seven bands away from the centromere on the right arm of chromosome llI, and we consider this to be the main site complementary to 5S RNA in the chironomid. This same RNA preparation specifically labeled the 56 EF region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…cold ethanol, after adding magnesium acetate to 1 mM. The precipitated material was resuspended in 3% potassium acetate pH 5.2 and reprecipitated with ethanol (Wen et al, 1974). U.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cold ethanol, after adding magnesium acetate to 1 mM. The precipitated material was resuspended in 3% potassium acetate pH 5.2 and reprecipitated with ethanol (Wen et al, 1974). U.v.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon-coated Collodion-covered grids were used; preparations were rotary-shadowed at a 7 ° angle with platinum/palladium 80 : 20. Acrylamide gel electrophoresis of the nucleic acids was according to procedures already described (Wen et al, 1974), except that 0.8% agarose was used to stabilize the gels and staining was done with 0.04% methylene blue (Peacock & Dingman, 1968). Escherichia coli ribosomal RNA (Sigma) mol.…”
Section: Methodsmentioning
confidence: 99%
“…Bridges went on to point out that the occurrence of homologies (in the sense of morphologically similar regions) at different sites along the same chromosome can be viewed as a "-demonstration that certain sections of normal chromosomes have actually been built up in blocks through such repeats-". But later several in situ hybridization studies indicated that ectopic pairing commonly involved the multiple sites of reiterated loci (Wen et al 1974, Pardue et al 1970, Henderson et al 1973. Zhimulev et al (2003) have compared the morphological characteristics of IH with other types of silenced chromatin such as pericentromeric heterochromatin and regions subject to position ef-fect variegation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Cohen (1976) supported the view of Kaufmann et al, (1948) who suggested that non-homologous pairing (ectopic pairing) may be due to the association of repeated gene sequences, but not necessarily highly repeated by recording it between two different 5S sites in the genome of D. funebris. Wen et al (1974) reported the clearly labelled interchromosomal connection between two of the nucleolar organisers in the polytene chromosome of Glyptotendipes barbipes. A similar observation has also been made by Henderson et al (1973) for human chromosomes carrying the nucleolus organisers.…”
Section: Discussionmentioning
confidence: 99%